How many premature deaths from pesticide suicide have occurred since the agricultural Green Revolution?. (2nd April 2020) - Karunarathne, Ayanthi; Gunnell, David; Konradsen, Flemming; Eddleston, Michael
Abstract: Introduction: The agricultural Green Revolution in the 1950s and 60s is thought to have averted many deaths from famine. However, it also introduced highly hazardous pesticides such as parathion and endrin into poor rural communities that were totally unequipped to store or use them safely. Pesticide self-poisoning rapidly became one of the two most common global means of suicide. Thus far, no attempt has been made to enumerate the total number of deaths that have occurred subsequent to the Green Revolution. Objective: To calculate plausible estimates for the total global number of pesticide suicides that have occurred since 1960. Methods: We performed a literature review on Medline and Embase databases to July 2019 to find papers that reported national or global numbers of pesticide suicides. We restricted our search to papers published in English. We used the search terms: pesticide) OR insecticide) OR paraquat) OR organophosphate) OR organophosphorus) OR agrochemical) AND suicide) OR "") OR deliberate) AND poison in all fields. These searches identified 2, 144 papers; a further 8 citations were added through the searching of reference lists and our own paper collections. 2, 136 papers were excluded as they contained no data on pesticide suicide, or were case reports, case series, or related to specific socio-demographic groups, or were non-human studies. This left 16 papers giving country specific or global pesticide suicide data. Long-term national trend in pesticide suicides: We found studies from one low- and middle-income country (Sri Lanka) that recorded long-term trends in suicide throughout the Green Revolution. These data showed a steady increase in suicides from 1960 to the early 1970s, with a more rapid increase from 1979 to 1984. The number of suicides plateaued until 1995, when they started a steady almost linear decrease that has continued at least until 2015. We used the Sri Lankan epidemiology as a model of the incidence of pesticide suicides in other low- and middle-income countries. Data from Bangladesh suggested that the decrease might have started in 2002. Estimating global numbers since 1960: Starting from a conservative estimate of zero deaths in 1960, the best estimate of the total global burden of pesticide suicides from 1960 to 2018 is 14, 272, 105 or 14, 936, 000 (depending on whether a fall in incidence began in 1995 or 2002), with a plausible range of 9, 859, 667 to 17, 303, 333 deaths. These are likely underestimates because suicide is illegal in many countries, and most pesticide suicides occur in poor rural areas without effective death registration systems. Conclusions: Pesticide self-poisoning has been a major clinical and public health problem in rural Asia for decades, while being long ignored. Most pesticide suicides are relatively impulsive with little planning: in the absence of highly hazardous pesticides, many people would have survived their suicidal impulse, gone on to find support amongst family, community, and health services, and lived a full life. Pesticide suicides must therefore be considered a category 4 occupation condition following Schilling's classification - if they had not been brought into rural communities for agricultural use, pesticide suicides would not have occurred. Preventing these deaths should be a global public health priority.